The Effect of the Aplton Model in Teaching Some Basic Skills on the Floor Exercise Mat - Rana Abdel Rahman Abdel Samad; Lamyaa Hassan Mohammed; Ghazi Lafta Hussein (دراسات وبحوث التربية الرياضية)
The aim of this research is to know the effect of the Ableton model in teaching some basic skills on the ground movements mat (straight forward roll, handstand, Arabic jump, front hands jump). We used the experimental design for two equal groups with pre- and post-tests. We chose from the College of Physical Education and Sports Sciences intentionally (the intentional method) to conduct the experiment. The control and experimental groups were chosen by simple random method (lottery). The control group (the model followed) was Section H (18) and the number of sample members was (15) students, the experimental group (Ableton model) was Section B (21) and its number was (15) students, the students excluded from the two sections were (9) students. The Appleton model has a positive effect on the excellence and raising the level of the experimental group students in learning the basic skills (the straight front step (dive), standing on the hands, the Arab jump, and the front hands jump) on the floor exercises mat for artistic gymnastics.